Urban street architecture, the K67 Kiosk - Rendla, Marta (Prispevki za novejšo zgodovino, 2023)
In the following contribution, the author presents the complex development and evolution of the universally and modularly designed K67 Kiosk – the famous red booth by the Slovenian architect and industrial designer Saša Janez Mächtig – from its conception in the second half of the 1960s through its upgrades and specialisation in the 1970s to today’s modernisation as an interactive self-service multipurpose kiosk for the twenty-first century, the K21. The K67 Kiosk – a product of urban street industrial design architecture – was created under the influence of the architectural trends at the time and due to the growing needs of the city and the development of urban service activities. The miniature street architecture, which used to house newspaper, tobacco, and food shops, small workshops, flower shops, parking and ticket booths, information and tourist offices, gatehouses, etc., became a part of the general urban culture of the former Yugoslav territory, the urban space of former Eastern European socialist countries, the collective consciousness and memory, as well as a cult product.
Keywords: industrijsko oblikovanje; Jugoslavija; kioski; modularna arhitektura; Slovenija